Embrioni crio-congelati inutilizzabili: la Corte costituzionale se ne lava le mani, ma qualcosa dice… (nota a C. cost., sent n. 84/2016) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The Constitutional Court Decision no. 84/2016 addresses a typical political question. The Court eludes the problem by means of a controversial “downgrading” of the balancing from a constitutional to a legislative level and declaring the question inadmissible. Nevertheless, behind the formal rejection, a possible solution on the merits comes up through the lines: a hypothetical different balancing in favour of health and scientific research would be not automatically unconstitutional, but it pertain only to the Legislator. Thus, although the Court could have adopted a “principled adjunctive” decision, it preferred not to decide at all, but at the same time it set the basis for a future legislative reforms in favour of the scientific research.
Keywords: unusable cryo-preserved embryos; political question; constitutional balance; legislative discretion; â€œprincipled adjunctiveâ€ decision as a possible alternative solution